Comparación de medios de cultivo con salinidad controlada en la enumeración de bacterias heterotróficas en una laguna costera - Sommaruga, Rubén (1989)
An efficiency comparison for counts of viable heterotrophic bacteria in a coastal lagoon was done for three media with different salinities. Water samples were taken along me salinity gradient (range 1-28 %), with and without lagoon communication with the sea. In all cases, the cstuarine mcdium wilh intermediate salt concentration gave the highest values of colony forming units and is more reliable.